ENVIRONMENTAL PROTECTION DURING CONSTRUCTION OF MOTORWAYS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
In this paper given and analysed are the factors related to the construction of motorways and having a negative impact on the environment. Given are the conditions o f the assessment of the impact of the motorways on the environment, arable land andforests and cultural heritage.